2013
DOI: 10.1111/trf.12492
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of blood donor screening for Babesia microti in endemic regions of the United States

Abstract: Background Babesia microti is the leading reported cause of red blood cell (RBC) transfusion-transmitted infection in the United States (US). Donor screening assays are in development. Study Design and Methods A decision analytic model estimated the cost-effectiveness of screening strategies for preventing transfusion-transmitted babesiosis (TTB) in a hypothetical cohort of transfusion recipients in Babesia-endemic areas of the US. Strategies included: (1) No screening, (2) Uniform Donor Health History Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…As an EIA in standard microplate format, it should be amenable to high-throughput processing and promises to meet cost-effectiveness criteria as set forth in recent analyses. 40 …”
Section: Discussionmentioning
confidence: 99%
“…As an EIA in standard microplate format, it should be amenable to high-throughput processing and promises to meet cost-effectiveness criteria as set forth in recent analyses. 40 …”
Section: Discussionmentioning
confidence: 99%
“…The economic impact assessment team noted that since 2014, three studies have been conducted on the cost effectiveness of B. microti screening with highly variable cost‐effectiveness results ranging from $54,000 to $83,000/quality‐adjusted life‐year (QALY) to $5.2 million/QALY and $8.8 million/QALY . Rather than undertake further cost‐effectiveness, we conducted an analysis of the number of infectious units that would be removed from the system through various testing methods and the cost of prevention.…”
Section: Assessing the Risk And Risk Management Options (Rbdm Stage 4)mentioning
confidence: 99%
“…Each has arrived at different conclusions regarding the cost effectiveness of TTB screening for similar programs. Two studies found that effective programs could be devised that would cost less than the 1 million dollars per QALY threshold [37,48]. One of these found that universal donor antibody screening for B. microti in endemic areas of the US is the most promising approach while the other found that universal PCR in four endemic states would be most cost effective.…”
Section: Cost Effectiveness Of Screeningmentioning
confidence: 99%